What are you so grumpy about? - Lichtenheld, Tom. (New York : Little, Brown, 2006)
Illustrations and simple text describe different reasons for being grumpy, such as eating "grown-up" cereal, getting a boring birthday present, doing chores, and being touched by your brother or sister.
Booklist
Publisher's Weekly
School Library Journal
2.2
3-6.
3-6
Keywords: Mood (Psychology) -- Juvenile fiction; Humorous stories; Mood (Psychology) -- Fiction; Humorous fiction; Mood (Psychology) -- Fiction